Elastic and Plastic Section Moduli of Steel Angles About Principal Axes - Ding, Yongcong; Madugula, Murty K.S. (Engineering Journal, 2004)
Steel angles are frequently subjected to bending moment due to self-weight, wind load, eccentricity of connections, etc. Depending on the width-to-thickness ratios and unbraced length-to-width ratios, they can develop full plastic moment of resistance under transverse loads. AISC Manual of Steel Construction (Third Edition) gives the elastic and plastic section moduli about the geometric axes (X and Y axes) only and not about the principal axes. There is a need to calculate elastic and plastic section moduli of angle sections about the principal axes for use in determining their bending strength. Based on the simplified assumption that the cross-section consists of two rectangles (i.e., ignoring the effect of toe and heel radii), formulas to locate the major and minor plastic principal axes and to determine the corresponding section moduli are derived in this technical note. The results of the computations for all of the angle sections listed in the AISC Manual (Third Edition) are tabulated.